Return of the sums

Calculus Level 3

n 0 n 2 ( n 1 ) n ! = a e . \displaystyle \sum_{n \ge 0} \dfrac{n^2(n-1)}{n!} = ae.

In the equation above, a a is a positive integer and e e is Euler's number. Find a a .

3 1 4 2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Chew-Seong Cheong
Feb 12, 2018

S = n 0 n 2 ( n 1 ) n ! Summand = 0 , when n = 0 , 1 = n = 2 n 2 ( n 1 ) n ! Note that n ! = n ( n 1 ) ( n 2 ) ! = n = 2 n ( n 2 ) ! = n = 0 n + 2 n ! = n = 0 n n ! + 2 n = 0 1 n ! Summand = 0 , when n = 0 = n = 1 n n ! + 2 n = 0 1 n ! = n = 1 1 ( n 1 ) ! + 2 n = 0 1 n ! = n = 0 1 n ! + 2 n = 0 1 n ! = 3 n = 0 1 n ! = 3 e \begin{aligned} S & = \sum_{n \ge 0} \frac {n^2(n-1)}{n!} & \small \color{#3D99F6} \text{Summand }= 0 \text{, when }n=0, 1 \\ & = \sum_{n=2}^\infty \frac {n^2(n-1)}{\color{#3D99F6}n!} & \small \color{#3D99F6} \text{Note that }n! = n(n-1)(n-2)! \\ & = \sum_{\color{#3D99F6}n=2}^\infty \frac n{(n-2)!} \\ & = \sum_{\color{#D61F06}n=0}^\infty \frac {n+2}{n!} \\ & = {\color{#3D99F6}\sum_{n=0}^\infty \frac n{n!}} + 2 \sum_{n=0}^\infty \frac 1{n!} & \small \color{#3D99F6} \text{Summand }= 0 \text{, when }n=0 \\ & = {\color{#3D99F6}\sum_{\color{#D61F06}n=1}^\infty \frac n{n!}} + 2 \sum_{n=0}^\infty \frac 1{n!} \\ & = \sum_{\color{#D61F06}n=1}^\infty \frac 1{(n-1)!} + 2 \sum_{n=0}^\infty \frac 1{n!} \\ & = \sum_{\color{#3D99F6}n=0}^\infty \frac 1{n!} + 2 \sum_{n=0}^\infty \frac 1{n!} \\ & = 3 \sum_{n=0}^\infty \frac 1{n!} \\ & = 3e \end{aligned}

a = 3 \implies a = \boxed{3} .

Jc 506881
Feb 13, 2018

n = 0 n 2 ( n 1 ) n ! = n = 0 n ( n 1 ) ( n 2 + 2 ) n ! = n = 0 n ( n 1 ) ( n 2 ) n ! + 2 n = 0 n ( n 1 ) n ! = d 3 d x 3 e x x = 1 + 2 d 2 d x 2 e x x = 1 = e + 2 e = 3 e \begin{aligned} \sum_{n = 0}^{\infty} \frac{n^2(n-1)}{n!} &= \sum_{n = 0}^{\infty} \frac{n(n-1)(n - 2 + 2)}{n!} \\ &= \sum_{n = 0}^{\infty} \frac{n(n-1)(n-2)}{n!}+ 2\sum_{n = 0}^{\infty} \frac{n(n-1)}{n!} \\ &= \frac{d^3}{dx^3}e^x|_{x = 1} + 2\frac{d^2}{dx^2}e^x |_{x=1} \\ &= e + 2e \\ &= 3e \end{aligned}

Akeel Howell
Feb 12, 2018

We are given n 0 n 2 ( n 1 ) n ! \displaystyle \sum_{n \ge 0} \dfrac{n^2(n-1)}{n!} .

We can rewrite this as n = 2 n ( n 2 ) ! = n 0 n + 2 n ! = 2 n 0 1 n ! + n 0 n n ! = 2 e + n 0 1 ( n 1 ) ! = 3 e . \displaystyle \sum_{n = 2}^{\infty} \dfrac{n}{(n-2)!} = \sum_{n \ge 0} \dfrac{n+2}{n!} \\ \displaystyle = 2\sum_{n \ge 0} \dfrac{1}{n!} + \sum_{n \ge 0} \dfrac{n}{n!} = 2e + \sum_{n \ge 0} \dfrac{1}{(n-1)!} = 3e.

Hence, we see that a = 3 a = \boxed{3} .

Piero Sarti
Feb 18, 2018

Let, S = n = 0 n 2 ( n 1 ) n ! Evaluating the first 2 terms, S = 0 + 0 + n = 2 n ( n 2 ) ! S = 2 + 3 1 ! + 4 2 ! + 5 3 ! + 6 4 ! + S = 2 + 3 + 4 × 1 2 ! + 5 × 1 3 ! + 6 × 1 4 ! + S = e + 3 + 3 × 1 2 ! + 4 × 1 3 ! + 5 × 1 4 ! + S = e + e + 1 + 2 × 1 2 ! + 3 × 1 3 ! + 4 × 1 4 ! + S = e + e + 1 + 1 + 1 2 ! + 1 3 ! + 1 4 ! + S = e + e + e = 3 e a = 3 \begin{aligned}\text{Let, } S = \sum_{n=0}^{\infty}{\dfrac{n^2(n-1)}{n!}} \\ \text{Evaluating the first 2 terms, } \\ S = 0 + 0 + \sum_{n=2}^{\infty}{\dfrac{n}{(n-2)!}} \\ S = 2 + \frac{3}{1!} + \frac{4}{2!} + \frac{5}{3!} + \frac{6}{4!} + \cdots \\ S = 2 + 3 + 4\times\frac{1}{2!} + 5\times\frac{1}{3!} + 6\times\frac{1}{4!} + \cdots \\ S = e + 3 + 3\times\frac{1}{2!} + 4\times\frac{1}{3!} + 5\times\frac{1}{4!} + \cdots \\ S = e + e + 1 + 2\times\frac{1}{2!} + 3\times\frac{1}{3!} + 4\times\frac{1}{4!} + \cdots \\ S = e + e + 1 + 1 + \frac{1}{2!} + \frac{1}{3!} + \frac{1}{4!} + \cdots \\ S = e + e + e = 3e \\ \therefore \boxed{a = 3} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...